Taxonomic studies on five species of the genus Colletotrichum - and D.K. AGARWAL, H.T. ROHANA WIJESEKARA* (Indian Phytopathology, 2006)
Five species of Colletotrichum viz. C. capsici, C. dematium, C. falcatum, C. gloeosporioides and C. lindemuthianum were examined for the classical morphotaxonomic criteria. It was observed that the dimensions of conidia, appressoria and setae are different from that observed by other authors and the ranges for each species were ammended.